Analysis of Silver Nanoparticles Synthesis, Characterization, and Biomedical Applications - Monika; Katare, Rajesh kr; Tripathi, SBL (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
This paper presents a comprehensive examination of the synthesis, characterization, and applications of silver nanoparticles (AgNPs) in biomedical fields. AgNPs exhibit exceptional properties, including antibacterial, antiviral, and antifungal activities, rendering them valuable in various biomedical applications. We explore diverse synthesis methods—chemical, physical, and biological—detailing their advantages and challenges. Through bibliometric analysis of 10,278 publications spanning 2010 to 2020, we identify trends in AgNPs research and synthesis techniques. Characterization methods crucial for understanding AgNPs’ physicochemical properties are discussed, encompassing spectroscopic, microscopic, and physicochemical analyses. We employ bibliometric clustering to elucidate AgNPs’ biomedical applications, which include antibacterial, antiviral, anticancer, bone healing, bone cement, dental, and wound healing applications. Our findings underscore the growing adoption of AgNPs in biomedicine due to their multifaceted properties and demonstrated efficacy. By examining synthesis methods, characterization techniques, and applications, this paper contributes to a deeper understanding of AgNPs’ role in advancing biomedical technologies. AgNPs offer promising solutions to various biomedical challenges, reflecting their increasing relevance in healthcare. This analysis provides insights into current research directions and highlights AgNPs’ potential for addressing critical healthcare needs.